Authoritative and Protective Insignia, Regalia and Symbols in Nubian Afro-Byzantine Rulers' Iconography - Steyn, Raita (Journal of early Christian history, 2017)
This article discusses the authority and protection insignia, regalia and symbols which are used in the Nubian Afro-Byzantine iconography of kings, eparchoi and other royals. They are discussed and analysedthrough the study of the most important frescos in Nubian medieval churches in terms of their position, function and meaning within the Byzantine and Afro-Byzantine context. The article reaches a number of conclusions referring to the religious, artistic, symbolic, political and institutional use and value of these representations of authority, protection and their connotations.